Studies on the Film Coating Potential of Anacardium Occidentale (Cashew Tree) Gum - Amekyeh, Hilda (2013)
A thesis submitted to the School of Graduate Studies in partial Fulfilment of the requirement for the Master of Philosophy (MPhil) Pharmaceutics Degree, 2012